Apolipophorin-III Acts as a Positive Regulator of Plasmodium Development in Anopheles stephensi - Dhawan, Rini; Gupta, Kuldeep; Kajla, Mithilesh; Kakani, Parik; Choudhury, Tania P.; Kumar, Sanjeev; Kumar, Vikas; Gupta, Lalita (Frontiers in Physiology, 2017)
Apolipophorin III (ApoLp-III) is a well-known hemolymph protein having a functional role in lipid transport and immune responses of insects. Here we report the molecular and functional characterization of Anopheles stephensi Apolipophorin-III (AsApoLp-III) gene. This gene consists of 679 nucleotides arranged into two exons of 45 bp and 540 bp that give an ORF encoding 194 amino acid residues. Excluding a putative signal peptide of the first 19 amino acid residues, the 175-residues in mature AsApoLp-III protein has a calculated molecular mass of 22 kDa. Phylogenetic analysis revealed the divergence of mosquitoes (Order Diptera) ApoLp-III from their counterparts in moths (Order: Lepidoptera). Also, it revealed a close relatedness of AsApoLp-III to ApoLp-III of An. gambiae. AsApoLp-III mRNA expression is strongly induced in Plasmodium berghei infected mosquito midguts suggesting its crucial role in parasite development. AsApoLp-III silencing decreased P. berghei oocysts numbers by 7.7 fold against controls. These effects might be due to the interruption of AsApoLp-III mediated lipid delivery to the developing oocysts. In addition, nitric oxide synthase (NOS), an antiplasmodial gene, is also highly induced in AsApoLp-III silenced midguts suggesting that this gene acts like an agonist and protects Plasmodium against the mosquito immunity.